Tank Pile Planning Using Standard Penetration Test Data Against Seismic Loads - Agustiar, Irawan; Akhmad, Andi Saputra; Nugroho, Dandy (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
This study stems from a question: “How should the foundation of a 2,000 m3 water tank be designed using standard penetration test (SPT) data for earthquake loads in accordance with SNI 1726:2019?” With a capacity of 2,000 m3, this tank has a significant volume and weight, making foundation analysis, especially regarding the effects of earthquakes, crucial, given that Indonesia is a region with high activity. SNI 1726:2019 provides technical guidelines for earthquake-resistant design for building and non-building structures, including tank foundations. The objective is to determine the detailed dimensions of a foundation that can withstand earthquake loads in accordance with SNI 1726:2019, thereby obtaining the dimensions of the pile cap along with the required reinforcement details, as well as the sufficient bearing capacity of the piles based on standard penetration test (SPT) data. To determine the bearing capacity of the piles, the empirical formula proposed by Terzaghi and Mayerhof is used. The planning results yielded pile cap dimensions of 1600 cm in diameter and 80 cm in thickness, using fc' 30 MPa concrete and D19-150 threaded reinforcement steel. There are 50 pile foundation points with 50 cm diameter spun piles at a depth of 16 m.